Brain Network Topology and Structural–Functional Connectivity Coupling Mediate the Association Between Gut Microbiota and Cognition - Zhang, Shujun; Xu, Xiaotao; Li, Qian; Chen, Jingyao; Liu, Siyu; Zhao, Wenming; Cai, Huanhuan; Zhu, Jiajia; Yu, Yongqiang (Frontiers in Neuroscience, 2022)
Increasing evidences indicated gut microbiota can influence cognition via the gut-brain axis, and brain networks play a critical role during the process. However, little is known about how brain network topology and structural-functional connectivity (SC-FC) coupling contribute to the gut microbiota-cognition. Fecal samples were collected from 157 healthy young adults and 16S amplicon sequencing was used to assess gut diversity and enterotypes. Topological properties of brain structural and functional networks were acquired by diffusion tensor imaging and resting-state fMRI data and further calculated the SC-FC coupling. 3-back, digit span, and Go/No-Go tasks were employed to assess cognition. Then, we tested for potential associations between gut microbiota, complex brain networks and cognition. Results showed that gut microbiota could affect the global and regional topological properties of structural networks, as well as node properties of functional networks. Of note, causal mediation analysis further validated that gut microbial diversity and enterotypes indirectly influence the cognitive performance by mediation of the small-worldness (Gamma and Sigma) of structure networks and some nodal metrics of functional networks (mainly distributed in cingulate gyri and temporal lobe). Specifically, gut microbes could affect the degree of SC-FC coupling in inferior occipital gyrus, fusiform gyrus, and superior frontal gyrus, medial, which in turn influence the cognition. Our findings revealed novel insights, which are essential to provide the foundation for previously unexplored network mechanism in understanding cognitive impairment, particularly with respect to how the brain connectivity participates in the complex cross-talk between gut microbiota and cognition.